To the 90th anniversary of traumatology-orthopaedics department of Dnipropetrovsk Medical Аcademy - Loskutov, Aleksandr; Oleynik, Aleksandr; Sinegubov, Dmitriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The article describes the main stages scientific, pedagogical, organizational and social activities of the Department of Traumatology and Orthopedics of the Dnipropetrovsk Medical Academy